The NAC transcription factor ANAC046 is a positive regulator of chlorophyll degradation and senescence in Arabidopsis leaves - Oda-Yamamizo, Chihiro; Mitsuda, Nobutaka; Sakamoto, Shingo; Ogawa, Daisuke; Ohme-Takagi, Masaru; Ohmiya, Akemi (Scientific reports, 2016)
Chlorophyll (Chl) degradation occurs during leaf senescence, embryo degreening, bud breaking, and fruit ripening. The Chl catabolic pathway has been intensively studied and nearly all the enzymes involved are identified and characterized; however, the molecular regulatory mechanisms of this pathway are largely unknown. In this study, we performed yeast one-hybrid screening using a transcription factor cDNA library to search for factors controlling the expression of Chl catabolic genes. We identified ANAC046 as a common regulator that directly binds to the promoter regions of NON-YELLOW COLORING1 , STAY-GREEN1 ( SGR1 ), SGR2 , and PHEOPHORBIDE a OXYGENASE . Transgenic plants overexpressing ANAC046 exhibited an early-senescence phenotype and a lower Chl content in comparison with the wild-type plants, whereas loss-of-function mutants exhibited a delayed-senescence phenotype and a higher Chl content. Microarray analysis of ANAC046 transgenic plants showed that not only Chl catabolic genes but also senescence-associated genes were positively regulated by ANAC046. We conclude that ANAC046 is a positive regulator of Arabidopsis leaf senescence and exerts its effect by controlling the expression of Chl catabolic genes and senescence-associated genes.